2011
DOI: 10.1021/ja208427j
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide as an Enzyme Inhibitor: Modulation of Activity of α-Chymotrypsin

Abstract: We have investigated the efficacy of graphene oxide (GO) in modulating enzymatic activity. Specifically, we show that graphene oxide can mimic as an artificial receptor and inhibit the activity of α-chymotrypsin (ChT), a serine protease. Most significantly, our data demonstrate that GO exhibits the highest inhibition dose response (by weight) for α-chymotrypsin inhibition compared to all other reported artificial inhibitors. Through fluorescence spectrometry and circular dichroism (CD) studies, we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
211
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(223 citation statements)
references
References 38 publications
12
211
0
Order By: Relevance
“…Apparently, the enzyme immobilization onto GO might be a result of the synergic effect of the different interactions. De et al [96] studied the interaction between GO and chymotrypsin and found that GO could strongly inhibit the activity of chymotrypsin, which might be due to the coexistence of anionic, hydrophobic, and π -π stacking interactions and a large surface area to mass ratio of GO. As pointed by Duinhoven et al the enzyme immobilization on solid substrate should be a comprehensive result of several attractive and repulsive interactions, and the exact interaction or " driving force " for it should be different for various classes of enzymes/proteins [121] .…”
Section: Noncovalent Adsorption Of the Protein/ Enzyme Molecules On Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the enzyme immobilization onto GO might be a result of the synergic effect of the different interactions. De et al [96] studied the interaction between GO and chymotrypsin and found that GO could strongly inhibit the activity of chymotrypsin, which might be due to the coexistence of anionic, hydrophobic, and π -π stacking interactions and a large surface area to mass ratio of GO. As pointed by Duinhoven et al the enzyme immobilization on solid substrate should be a comprehensive result of several attractive and repulsive interactions, and the exact interaction or " driving force " for it should be different for various classes of enzymes/proteins [121] .…”
Section: Noncovalent Adsorption Of the Protein/ Enzyme Molecules On Tmentioning
confidence: 99%
“…Generally, the conformation of the enzymes might be changed after being immobilized on solid substrate surface, thus, their activities could be affected upon immobilization [96] . The effect of the solid substrate on the immobilized enzymes in many cases is unpredictable because its surface structure and property are unknown.…”
Section: Catalytic Performances Of the Go-immobilized Enzymesmentioning
confidence: 99%
“…Because of its high surface-area-to-mass ratio, ceMoS 2 also possesses loading capacities on par with GO, the current best-in-class. [15] Clearly, ceMoS 2 possesses many desirable traits present in the aforementioned photothermal agents.…”
mentioning
confidence: 99%
“…This value is significant, as it demonstrates that ceMoS 2 has a ChT doseinhibition capacity comparable to GO, which is the current benchmark material (full comparison in the Supporting Information). [15] To show that the host-guest interaction between ChT and ceMoS 2 is reversible, we incubated ChT with 11 ppm of ceMoS 2 (full inhibition concentration) in media of increasing ionic strength to negate electrostatic interactions. [27] In one set of experiments, ceMoS 2 was added to ChT in media prespiked with NaCl (pre-incubated).…”
mentioning
confidence: 99%
See 1 more Smart Citation